Fighting against allies : an examination of "national caveats" within the NATO-led International Security Assistance Force (ISAF) campaign in Afghanistan & their impact on ISAF operational effectiveness, 2002-2012 - Kingsley, Regeena (Massey University, 2014)
During the last twenty years, it has become an increasingly common practice for national governments to impose restrictive “national caveat” rules of engagement on the forces they contribute to multinational security operations. These national caveats have regularly led to security crises within these multinational missions, most notably in Rwanda, Bosnia and Kosovo. However, due to government sensitivity, combined with the highly-classified nature of these national caveat rules, no rigorous academic analysis has ever been conducted on this problematic issue and its effects within international security endeavours. The result has been a large ‘caveat gap’ within academic defence literature. This thesis is the first in-depth, academic examination of the issue of national caveats and their effects within multinational security operations, and is focused on the multinational NATO-led ISAF campaign in Afghanistan. Drawing from new caveat information, including the revelations contained within the cache of diplomatic cables released by Wikileaks in 2010-2011, this research analyses the issue of national caveats within the ISAF operation in order to determine both the extent of the national caveat issue within the ISAF mission, and the impact these caveats have had on overall operational effectiveness within the campaign, over the period of a decade of warfare between 2002-2012. The research utilises the fundamental military principle of “unity of effort”, essential for attaining operational effectiveness in any multinational operation involving disparate national forces, as an analytical lens to analyse the impact of national caveats on ISAF operational effectiveness. It analyses the impact of government-imposed, politico-military caveats on unity of effort among the ISAF’s security forces conducting security operations within the overarching counter-insurgency (COIN) campaign. ISAF security operations are critical for the success of the ISAF COIN campaign, because basic security is a prerequisite for all other ISAF stability operations to proceed along the other lines of operation. The study analyses: firstly, the ability of ISAF security forces to be unified in their tasking, given these caveat restraints; and secondly, the reality of unity of effort in practice among these forces, in the course of planning and executing on-the-ground security operations within Afghanistan. The findings are then discussed to assess the impact of national caveats on ISAF unity of effort as a whole over the decade, and subsequently, the overall impact of caveated ISAF forces on operational effectiveness within the NATO-led Afghan mission. This study found that national caveats continuously constrained approximately a quarter of the entire ISAF force between 2002-2012, regardless of fluctuations in total force numbers over the decade. An extensive range of more than 200 caveats were imposed by various NATO and Partner nation governments on ISAF forces over this time period, which hindered ISAF security operations throughout Afghanistan and led to a resultant loss of time and progress along the critical security line of operation within the campaign. Combat caveats, in particular, seriously compromised the ability of ISAF security forces, including large Lead Nation contingents in the northern and western ISAF sectors, to conduct the full range of operations necessary to protect the Afghan population from insurgents, and to achieve the mission of bringing security and stability to Afghanistan. In addition, these combat caveats have: disunified the ISAF coalition; fractured the NATO alliance; geographically and operationally divided the ISAF operation; and enabled the insurgent Enemy in Afghanistan. Furthermore, the existence of caveated national contingents within the total ISAF force has not only seriously and fundamentally compromised unity of effort within the mission, but has also had a detrimental impact on the operational effectiveness of the ISAF operation as a whole, characterised by the delayed attainment of mission objectives and an ineffective prosecution of the COIN campaign. Government-imposed national caveat rules of engagement have thereby compromised the multinational ISAF operation for over a decade within the Afghan theatre of war, and jeopardized the operational effectiveness and success of this important multinational security campaign. In conclusion, national caveats are potential guarantors of disunity of effort and operational ineffectiveness within every multinational operation in which they are present.
Keywords: National caveats; North Atlantic Treaty Organization (NATO); International Security Assistance Force (ISAF); Afghanistan; Multinational security operations; NATO security forces